The Influence of Authentic Leadership and Work Engagement on Employee Performance through Competency as an Intervening Variable at PT Tritama Jaya Wisata - Azizah, Zahra Nur; Wardhani, Nia Kusuma (Indonesian Journal of Business Analytics, 2024)
The research aims to determine the effect of authentic leadership and work engagement on employee performance using the intervention variable PT Tritama Jaya Wisata. The research method used was quantitative, using saturated samples taken from 45 respondents from all company employees. Analysis was carried out using structural equation models and Partial Least Squares (PLS) software. The research results show that leadership and work involvement have a positive and significant effect on employee performance, with an indirect influence on the competency variable.